EMPLOYEE TALENT IN DEVELOPMENT OF ORGANIZATION - Jaremczuk, Kazimierz; Mazurkiewicz, Anna (Journal of Positive Management, 2014)
The changes in the environment of the organization, particularly globalization, and changes in the demographics, as well as changes in the expectations and requirements of employees or customers, cause that current solutions are inadequate to the new conditions of operation, resulting in the inefficiency and ineffectiveness. Organizations must therefore constantly improve their operations. This requires a new approach, including one in human resource management, which is particularly a challenge to the best performing employees with great potential or talented employees. The ability to attract and retain talent in the organization is important for the ongoing operation and development of the organization. The purpose of this study is to show the importance of talent in the development of the organization. This objective required the identification of the conditions of interest and talent in the organization to a multi-faceted understanding of the concept of talent (with particular emphasis on the organizational aspect). It also drew attention to the issue of the development of talent. Contemplations have been carried out in the context of the organization.